1997
DOI: 10.1016/s0035-9203(97)90089-4
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis and reproductive health in Ecuador

Abstract: A retrospective study was performed comparing the number of spontaneous abortions in a hyperendemic area for onchocerciasis in Ecuador before and after invermectin treatment with that of a comparable non-endemic area. The frequency of spontaneous abortions was associated with a change in the community microfilarial load, suggesting that there may be a relationship between spontaneous abortions and infection with Onchocerca volvulus. In the endemic area, a significantly greater rate of spontaneous abortions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The question asked was whether the participant was born at term (pregnancy had completed nine months). A study in Ecuador suggested that onchocerciasis may be associated with an increased risk of spontaneous abortions [38]. In this study, the effects of onchocerciasis on preterm birth were not investigated, but as spontaneous abortions have been associated with preterm birth, it is possible that onchocerciasis could lead to preterm birth [39].…”
Section: Discussionmentioning
confidence: 93%
“…The question asked was whether the participant was born at term (pregnancy had completed nine months). A study in Ecuador suggested that onchocerciasis may be associated with an increased risk of spontaneous abortions [38]. In this study, the effects of onchocerciasis on preterm birth were not investigated, but as spontaneous abortions have been associated with preterm birth, it is possible that onchocerciasis could lead to preterm birth [39].…”
Section: Discussionmentioning
confidence: 93%
“…Marriage prospects, often an important part in life in endemic areas, are influenced by NTDs, particularly when an NTDs changes the physical appearance and, or someone's physical capabilities, which is the case for NTDs such as podoconiosis, onchocerciasis and cutaneous leishmaniasis (Chahed et al, 2016;Dunn et al, 2015;Ozano et al, 2020;Tsegay et al, 2018). To give an example, onchodermatitis, caused by onchocerciasis, is known as "the disease that prevents a girl from getting married" in certain parts of Nigeria (Dunn et al, 2015;Guderian et al, 1997). The influence of NTDs on marriage prospects are seen for both men and women (Chahed et al, 2016).…”
Section: Gender-specific Stigma and Health-seeking Behaviourmentioning
confidence: 99%
“…The severity of onchocerciasis and its associated itching is an independent predictor of a shorter lactation period [22]. An O. volvulus infection in pregnant women may be associated with an increased risk of spontaneous abortions [23] and with earlier and more severe O. volvulus infections in their offspring [24].…”
Section: What Is Known About the Negative Impact Of Onchocerciasis In Pregnancymentioning
confidence: 99%
“…In the same period, the incidence rate of spontaneous abortions in the non-endemic area was 1.3/1000 myar. An MDA with ivermectin every six months started in 1990 in the hyper-endemic area and 90−95% of those eligible were treated [23]. This resulted in a dramatic decline in community mf load to negligible levels by 1996 [23].…”
Section: The Effect Of Ivermectin Treatment Of O Volvulus Infected Pregnant Women On Pregnancy Outcomesmentioning
confidence: 99%